REV-ERB is essential in cardiac fibroblasts homeostasis - Luo, Xiaokang; Song, Shiyang; Qi, Lei; Tien, Chih-Liang; Li, Hui; Xu, Weiyi; Mathuram, Theodore Lemuel; Burris, Thomas; Zhao, Yuanbiao; Sun, Zheng; Zhang, Lilei (Frontiers in Pharmacology, 2022)
REV-ERB agonists have shown antifibrotic effects in the heart and other organs. The function of REV-ERB in the cardiac fibroblasts remains unstudied. Here, we characterize the functional difference of REV-ERB in mouse embryonic fibroblasts and cardiac fibroblasts using genetic deletion of REV-ERBα and ß in vitro. We show that REV-ERB α/β double deleted cardiac fibroblasts have reduced viability and proliferation, but increased migration and myofibroblasts activation. Thus, REV-ERB α/β has essential cell-autonomous role in cardiac fibroblasts in maintaining them in a healthy, quiescent state. We also show that existing REV-ERB agonist SR9009 strongly suppresses cardiac fibroblasts activation but in a REV-ERB-independent manner highlighting the need to develop novel REV-ERB agonists for treating cardiac fibrosis.